The effect of Bpsl0279 mutation on biofilm formation in Burkholderia pseudomallei - Pimthong, Supaporn; Sermswan, Rasana W.; Ernst, Robert K.; Wongratanacheewin, Surasakdi (Asia-Pacific Journal of Science and Technology, 2023)
Burkholderia pseudomallei is a causative agent of a fatal disease, melioidosis, which needs prolonged antibiotic treatment. It can produce biofilms that play some roles in either antibiotic resistance or relapse. Knowledge related to gene(s) that controlling biofilm formation in B. pseudomallei is still limited. From bioinformatics analysis, bpsl0279 and bpsl1080, the hypothetical genes in B. pseudomallei K96243, were found to be homologous with some of 80 biofilm related genes in other bacteria. Reverse transcription polymerase chain reaction (RT-PCR) showed their expression to be higher when growing in biofilm conditions compared to planktonic. Mutagenesis of bpsl0279 gene led to significantly lower biofilm productions. Approximately 75% of biofilm formation was reduced in Δbpsl0279 in static and easily observed in dynamic laminar shear conditions that can be restored by its complementation. The Δbpsl0279 formed only small microcolonies of 10-20 µm in diameter while the wild type established the roughness macrocolonies (> 50 µm) and reached 100 µm after 48 h. In addition, gfp-tagged wild type attached to the glass surface (264 ± 32 cells/field) significantly better than the mutants (120 ± 30 cells/field). The bpsl0279 was later reported as a putative flagella brake protein YcgR1 and was homolog with bth_i0249 in Burkholderia thailandensis. This gene contains PilZ domain, of which is a c-di-GMP binding and involved in many aspects of biofilm formation. Our study concluded bpsl0279 to be involved in the early stage of biofilm formation that may be a good target to interrupt for the benefit of treatment.